Catheter related blood stream infection (CRBSI) in esrd subjects undergoing haemodialysis via temporary central venous catheter at HUSM: a retrospective cohort review of 2 year data - Mohd Nawi, Nor Azilawati (2015)

(untitled)
Introduction: Since its introduction in 1964, haemodialysis has become one of the main modalities for the treatment of end-stage renal disease (ESRD). Central venous catheter (CVC) has become an important means in providing vascular access for haemodialysis treatment. Due to its nature as an indwelling catheter, there is an increased risk of developing catheter-related bloodstream infections (CRBSI). Hence, identifications of relevant risk factors for CRBSI development has become the paramount objective of this research endeavour. Methodology: This is a retrospective cohort study involving a review of the medical records of 116 ESRD Hospital USM (HUSM) on haemodialysis via CVC from 1st January 2013 until 31st October 2014. Relevant details on the identified CRBSI risk factors such as age, gender, comorbidities, length of hospital stay prior to CVC insertion, duration of catheterization, HbA1c level, catheter insertion sites, haemoglobin level, WBC, serum albumin and urea levels, and aetiologies of End Stage Renal Disease (ESRD) were collected. The data was analysed using multiple logistic regression and the probability equation for predicting the development of CRBSI was computed. Level of significance was fixed at 0.05. Results: The prevalence of CRBSI is 19% (95% CI 11.9,26.1) with CRBSI rate of 3.5 bacteraemia per 1000 catheter days. S. aureus (including MRSA) are the main microorganisms isolated among CRBSI cases (45.4%), followed by P.aeruginosa (22.7%) and others. Most of microbial isolates are susceptible to at least one type of antibiotics. Three significant risk factors for CRBSI were identified from multiple logistic regression analysis; duration of hospital admission before catheterization (adjusted OR:1.118 (95% CI: 1.030, 92.805), p value = 0.004), duration of catheterization in days (adjusted OR: 0.965 (95% CI 0.939, 0.992), p value = 0.005) and HbA1c levels ( i) HbA1c 6.6-8.0% (adjusted OR: 1.143 (95% CI: 0.249,5.247), p value = 0.849) and ii) HbA1c ≥8.0% (adjusted OR: 5.613 (95% CI 1.023, 30.792), p value = 0.047). Conclusion: The prevalence and CRBSI rate are comparable with other studies. Gram-positive cocci are still the predominant species isolated from HD subjects with CVC. Length of hospital stay prior to catheter insertion, duration of catheterization and HbA1c level were significant risk factors identified for CRBSI.